2021
DOI: 10.21123/bsj.2021.18.4.1163
|View full text |Cite
|
Sign up to set email alerts
|

A Prevalence study of Entamoeba spp. in Basrah Province using Different Detection Methods

Abstract: This study aims to determine the prevalence of Entamoeba histolytica, Entamoeba dispar and Entamoeba moshkovskii by three methods of diagnosis (microscopic examination, cultivation and PCR) that were compared to obtain an accurate diagnosis of Entamoeba spp. during amoebiasis. Total (n=150) stool samples related to patients were (n = 100) and healthy controls (n= 50). Clinically diagnosed stool samples (n=100) were collected from patients attending the consultant clinics of different hospitals in Basrah during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Se usa un líquido de alta densidad y los elementos de interés flotaran en este. (21) La modificación de la técnica es más usada, donde se omite la centrifugación de la muestra y en dos fases de sedimentación se obtiene al parásito que se desea estudiar en un medio con sulfato de cinc. (15,21) 91 % 83 % Método estandarizado y de fácil realización 21 .…”
Section: Técnica De Faustunclassified
See 3 more Smart Citations
“…Se usa un líquido de alta densidad y los elementos de interés flotaran en este. (21) La modificación de la técnica es más usada, donde se omite la centrifugación de la muestra y en dos fases de sedimentación se obtiene al parásito que se desea estudiar en un medio con sulfato de cinc. (15,21) 91 % 83 % Método estandarizado y de fácil realización 21 .…”
Section: Técnica De Faustunclassified
“…Los elementos para identificar se obtienen en un medio limpio que permite examinar la lámina de forma rápida. (21) Existen problemas cuando se manipulan muestras con gran contenido de grasas. (21) Es necesario usar una muestra con concentraciones de parásitos conocidos (control positivo).…”
Section: Técnica De Faustunclassified
See 2 more Smart Citations
“…Molecular studies have shown that the prevalence of E. dispar is 10 times higher than that of E. histolytica worldwide [ 12 , 13 ]. Also, precise differentiation and identification of the pathogenic and non-pathogenic species and strains would be of primary importance from a therapeutic point of view [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%